Google Analytics - Cutroni, Justin (O'Reilly, 2010)
Do you know what people do when they visit your website or web app? Or how much the site contributes to your bottom line? Google Analytics keeps track and makes it easy for you to learn precisely what's happening. This hands-on guide shows you how to get the most out of this free and powerful tool -- whether you're new to Google Analytics or have been using it for years. Google Analytics shows you how to track different market segments and analyze conversion rates, and reveals advanced techniques such as marketing-campaign tracking, a valuable feature that most people overlook. And this practic.